High Carrier Mobility, Electrical Conductivity, and Optical Transmittance in Epitaxial SrVO3 Thin Films. (10th February 2019) - Mirjolet, Mathieu; Sánchez, Florencio; Fontcuberta, Josep
Abstract: The urgent need for more performant transparent conducting electrodes is stimulating intensive research on oxide thin films based on early transition metals (e.g., V, Nb, Mo, etc.), where it is expected that the partially occupied (i.e., nd 1, nd 2 …) conduction band will give rise to metallic conductivity. Growing thin films of these oxides typically requires an extremely low oxygen pressure. However, in growth methods involving hyperthermal kinetics (such as pulsed laser deposition), this may have severe detrimental effects on the electrical and optical properties of the film. Here, it is shown that the use of a nonreactive gas during a pulsed laser deposition process allows epitaxial SrVO3 films to be obtained with low room temperature resistivity (ρ ≈ 31 μΩ cm), large carrier mobility (μ ≈ 8.3 cm 2 V −1 s −1 ), and large residual resistivity ratio (RRR ≈ 11.5), while improving optical transparency in the visible range. It is argued that the success of this growth strategy relies on the modulation of energetics of plasma species and a concomitant reduction of defects in the films. These findings may find applications in other oxide‐based thin film technologies (i.e., ferroelectric tunnel memories, etc.) where growth‐induced point effects may compromise functionality. Abstract : Transparent conductors are pivotal to the information society, and early transition metal oxides, such as SrVO3, are predicted to play a big role. However, the growth of high‐quality SrVO3 thin films is challenging. The use of an inert gas during pulsed laser deposition allows for SrVO3 films with enhanced electrical and optical properties to be obtained, thus solving current bottlenecks.